Glycated Albumin and Continuous Glucose Monitoring Metrics in Dogs with Diabetes Mellitus: A Pilot Study - Soon-Chan Kwon; Ju-Hyun An; Dong-Hoo Kim; Hwa-Young Youn (Animals)
Diabetes mellitus (DM) is one of the most common endocrine disorders in dogs. Glycated albumin (GA), a biomarker of short-term glycemia, may offer a valuable tool for assessing glycemic control in dogs with DM. This pilot study evaluated the correlation between GA and conventional glycemic markers and continuous glucose monitoring (CGM)-derived metrics in dogs. A total of 30 dogs were included in this prospective pilot study, comprising dogs with diabetes mellitus (n = 10) and healthy controls (n = 20). Of these, 11 dogs that lacked anemia, hypoalbuminemia, or azotemia and whose owners consented to 14-day CGM were analyzed for sensor-based metrics (dogs with diabetes, n = 7; controls, n = 4). Across the full cohort, GA showed significant correlations with fructosamine and HbA1c, while within the CGM subset, GA was significantly associated with mean glucose level, TIR2, and TAR2. These findings suggest that GA, in conjunction with fructosamine and HbA1c, offers valuable insights into glycemic control over a 2-week period and could serve as a reliable biomarker for glucose monitoring in dogs with diabetes.